Attitude that Matters - Purhonen, Tiina (Nordlit, 2007)
In this article, I compare the operativity of radical avant-garde and new dialogical art forms from one selected viewpoint. I discuss the issue of the artist’s attitude as a significance-producing element in the artwork. For decades, artist-issued interpretation of art has been problematic. Thus it is interesting to question the significance of the strong definition of the artist’s attitude, inherent in the theories of the new dialogical art. New dialogical art-forms are for example new genre public art, community art, socially engaged art, public engaged art, littoral art, activist art, dialogical art, and conversational art. In the Finnish discussion, the concept of community art is the one most commonly used.